Biodegradation of fats, oil and grease using microorganisms isolated from palm oil mill effluent - Al-Khatib, Ma'an Fahmi Rashid; Alqedra, Fadi I. A.; Alam, Md Zahangir (IIUM Press, 2023)
The biodegradation of fat, oil, and grease (FOG) is important in water pollution control and wastewater management. In this study, the viability of FOG-degrading microorganisms on palm oil biodegradation was assessed. Seven strains capable of degrading FOG were isolated from palm oil mill effluent (POME). The potential bacterial strains were selected based on Tween-80-degrading ability. Micrococcus lylae strain DSM 20315 showed the highest growth compared to the other strains. Hence, it was selected for FOG degradation test. The biodegradability was performed as a function of pH (6, 7, 8), initial oil concentration (1, 3, 5% v/v), and inoculum concentration (2, 6, 10% v/v). Optimization of these parameters of palm oil degradation was studied using 2-level factorial design. The maximum oil degradation was 68%, obtained at pH 6, initial oil concentration 1 % v/v, and bacterial inoculum concentration of 10 % v/v. The lowest oil degradation obtained was 22%. The initial oil concentration followed by bacterial inoculum concentration enhanced the removal efficiency of FOG, but the pH level did not significantly promote the degradation rate. As a result, the optimum process conditions for maximizing oil degradation were at pH 6, initial oil concentration 1 %v/v, and bacterial inoculum concentration of 10 %v/v.